Trans-regulatory variant network contributes to missing heritability - Vanessa Pereira; Elena Kuzmin (Cell Genomics, 2024)
In a recent Cell Genomics article, Tsouris et al.1 analyze the transcriptomes of a large diallel panel of hybrids from Saccharomyces cerevisiae natural isolates to study cis- and trans-regulatory changes underlying gene expression variation. Vanessa Pereira and Elena Kuzmin discuss the authors’ findings and the wider context in missing heritability research in this preview.